2015
DOI: 10.1016/j.neuroscience.2015.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Right hemisphere dominance directly predicts both baseline V1 cortical excitability and the degree of top-down modulation exerted over low-level brain structures

Abstract: HighlightsLine bisection predicts V1 excitability.Line bisection predicts degree of VOR modulation.Line bisection correlates with tDCS-mediated vestibular-nystagmus suppression.Degree of nystagmus suppression is a bio-marker of right hemisphere dominance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 19 publications
5
18
0
Order By: Relevance
“…Rather, it is the degree of cortically mediated suppression of the brainstem VOR that correlates with the anxiety scores, implying a cortically‐controlled re‐scaling of brainstem‐cortical interactions. In line with this, our previous findings have demonstrated that the nystagmus suppression index correlates with cognitive biases such as numerical magnitude perception and spatial attention (Arshad et al., , ), further supporting the notion of a brainstem‐cortical re‐scaling network.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Rather, it is the degree of cortically mediated suppression of the brainstem VOR that correlates with the anxiety scores, implying a cortically‐controlled re‐scaling of brainstem‐cortical interactions. In line with this, our previous findings have demonstrated that the nystagmus suppression index correlates with cognitive biases such as numerical magnitude perception and spatial attention (Arshad et al., , ), further supporting the notion of a brainstem‐cortical re‐scaling network.…”
Section: Discussionsupporting
confidence: 83%
“…With respect to vestibular processing, it has been shown that in right‐handed individuals predominant processing of vestibular signals occurs in the right hemisphere, whereas in left‐handers, the left hemisphere is dominant (Arshad et al., ; Dieterich et al., ; Nigmatullina et al., ). Furthermore, the degree of right hemisphere dominance in the vestibular system has been shown to influence both cortical (i.e., early visual cortex excitability) and brainstem (i.e., modulation of the vestibulo‐ocular reflex) functions (Arshad et al., ). Additionally, right hemisphere vestibulo‐cortical dominance has been shown to influence the modulation of vestibular thresholds following a change in cortical excitability (Bednarczuk et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations